A Single Unit Concept And Design Of A High Maneuverability Mobile Robot - Awi, Nurul Busra (Universiti Sains Malaysia, 2017)
The aim of this project is to design and produce a mobile robot as a tool that could replace humans to perform certain tasks such as search, inspection, navigation and rescue in hazardous environments. The mobile robot has the ability to move in the environment such as air, soil and water. Some types of mobile robots that have been widely developed such as legged robots, wheeled robot with no arms, wall climbing robot and robot amphibians. The mobile robot is also known as bio-inspired robot. Snake robot is one example of a mobile robot. Snake robots are suitable for environment that is very limited because of the small cross section and highly redundant kinematics enables them to enter and move through narrow spaces. Robot snake promising mechanism for real-world applications such as search and rescue in destroyed city and industrial inspection. The degree of freedom gives them the potential to adapt to complex environments for confined spaces. Snake robots offer advantages over traditional mobile robots because they provide properties that can be achieved especially in an environment that convoluted. Thus, a mobile robot is generated using CAD software systems of SolidWorks and a prototype is produced to test it abilities. Physical appliances that have been used are an Arduino UNO, servo motors, and other electrical equipment. After that, the functional test and mechanism of the snake robot prototype has been carried out.